Characterization of the circadian clock in Hooded Seals (Cystophora Cristata) and its interaction with mitochondrial metabolism A multi-tissue comparison and cell culture approach - Kante, Fayiri (UiT Norges arktiske universitet, 2021)
Circadian rhythms regulate living organisms over a 24h period. From daily activity to cellular function. The polar regions are subject to different photoperiods across the year, which impact the environmental conditions on a seasonal and daily basis. Evidence of crosstalk between circadian core clock genes and hypoxia with genes involved the mitochondrial dynamics, as well as oxygen sensing, provide a basis to study those mechanisms in a model which faces those 2 challenges. The hooded seal (Cystophora Cristata) is an expert diver, with excellent hypoxia tolerance, and an arctic mammal exposed to the special light environment. The primary aim of this study was to characterize the circadian clockwork in the hooded seal using in-vivo sampling and hooded seal skin fibroblasts. The secondary aim was to explore the clockwork and the variation mitochondrial metabolism in a circadian context with the culture of hooded seal skin fibroblasts. We show that the clock genes are expressed in different seal tissues without a marked difference between midday and midnight. Nevertheless, seal skin fibroblasts respond to treatments designed to entrain the circadian clockwork and showed a significant circadian oscillation in the key clock genes; PER-2, ARNTL, NR1D1. Finally, we showed that there is a time-of-day variation in the respiratory capacity of mitochondria in seal skin fibroblasts and in MFN1, a gene involved in mitochondrial dynamics. Overall, this thesis provides new knowledge on the circadian rhythm in seals and how mitochondrial metabolism may be influenced. These data encourage further research to depict mitochondrial dynamics and metabolism in a circadian and hypoxic conditions, as well as animal circadian behavior for an integrative perspective.